Mechanism Analysis and Parameter Optimization of Mega-Sub-Isolation System - Xiangxiu Li; Ping Tan; Xiaojun Li; Aiwen Liu (Shock and Vibration)
The equation of motion of mega-sub-isolation system is established. The working mechanism of the mega-sub-isolation system is obtained by systematically investigating its dynamic characteristics corresponding to various structural parameters. Considering the number and location of the isolated substructures, a procedure to optimally design the isolator parameters of the mega-sub-isolation system is put forward based on the genetic algorithm with base shear as the optimization objective. The influence of the number and locations of isolated substructures on the control performance of mega-sub-isolation system has also been investigated from the perspective of energy. Results show that, with increase in substructure mass, the working mechanism of the mega-sub-isolation system is changed from tuned vibration absorber and energy dissipation to seismic isolation. The locations of the isolated substructures have little influence on the optimal frequency ratio but have great influence on the optimal damping ratio, while the number of isolated substructures shows great impact on both the optimal frequency ratio and damping ratio. When the number of the isolated substructures is determined, the higher the isolated substructures, the more the energy that will be consumed by the isolation devices, and with the increase of the number of isolated substructures, the better control performance can be achieved.